Effective Levels of Chicken Feather Flour as a Supplementary Feed for Increase Broiler Chicken (Gallus domesticus L) Body Weight - -, Asiah; -, Khairil; Rizki, M. Aziz; -, Abdullah; -, Iswadi (Kalwedo Sains (KASA), 2023)
Broiler chickens have been widely eaten and bred because they are cheap in the form of meat. But the case in broiler farming is the high price of commercial feed. In view of this reality, it is necessary to find an alternative to the use of feed ingredients that do not compete with humans and their availability is quite abundant at an affordable price, namely the use of chicken feather waste as animal feed. This research aims to determine the content of chicken feather flour which is efficiently used as additional feed for broiler chickens. The research procedure used was an Experiment with 4 treatments and 6 replications, namely P0 = control (100% bran feed), P1 = 95% bran feed + 5% chicken feather meal, P2 = 90% bran feed + 10% chicken feather meal, P3 = 85% bran feed + 15% chicken feather flour. Information was analyzed by Analysis of Variance (ANOVA). The results of the research prove that giving chicken feather flour as additional feed for weight gain of broiler chickens has a significant effect on weight gain of broiler chickens. The conclusion of the research is: The content of chicken feather flour which is efficiently used as additional feed for broiler chickens is 10%